2021
DOI: 10.3390/nano11092438
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Coated PLGA Nanoparticles Loaded with Peganum harmala Alkaloids with Promising Antibacterial and Wound Healing Activities

Abstract: Wound healing is a major healthcare concern, and complicated wounds may lead to severe outcomes such as septicemia and amputations. To date, management choices are limited, which warrants the search for new potent wound healing agents. Natural products loaded in poly (lactic-co-glycolic acid) (PLGA) coated with chitosan (CS) constitute a promising antibacterial wound healing formulation. In this work, harmala alkaloid-rich fraction (HARF) loaded into PLGA nanoparticles coated with chitosan (H/CS/PLGA NPs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 50 publications
3
36
1
Order By: Relevance
“…The stability constant of the asplatin/PSC4 inclusion complex found utilizing our previously reported method [16] was 9.1 × 104 M −1 , corresponding to a complexation free energy of −6.8 kcal mol −1 . This value is within the stability constant range (0.001 × 10 4 to 16 × 10 4 M -1 ) of host-guest complexes designed for drug delivery applications [29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Asplatin/psc4: Uv-vis Spectroscopy Analysissupporting
confidence: 66%
“…The stability constant of the asplatin/PSC4 inclusion complex found utilizing our previously reported method [16] was 9.1 × 104 M −1 , corresponding to a complexation free energy of −6.8 kcal mol −1 . This value is within the stability constant range (0.001 × 10 4 to 16 × 10 4 M -1 ) of host-guest complexes designed for drug delivery applications [29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Asplatin/psc4: Uv-vis Spectroscopy Analysissupporting
confidence: 66%
“…where S 0 is the intrinsic solubility, and K 1:1 is the stability constant. The designed HARF-HPßCD complex was co-loaded with AA into PLGA NPs coated with PEG (HARF-HPßCD/AA@PLGA-PEG NPs) using the W/O/W multiple emulsionsolvent evaporation method, as previously reported with some modifications [3,7,33,34].…”
Section: Phase Solubility Studymentioning
confidence: 99%
“…Pharmaceutics 2022, 14, 142 2 of 13 The seeds of P. harmala are rich in harmala alkaloids such as quinazoline and β-carboline alkaloids. The major alkaloid, harmine, is responsible for the various pharmacological activities of the harmala seeds [5][6][7]. Several studies have reported the promising antimicrobial activities of P. harmala extracts [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the chitosan-coated NPs were challenged against S. aureus and E. coli using in vitro broth dilution method. The loaded chitosan-coated NPs improved the antibacterial potential against E. coli and S. aureus [179]. In another research effort, chitosan-coated NPs comprising PLGA and PVA loaded with benzalkonium bromide were evaluated in an in vitro biofilm assay and an in vivo murine MRSA-infected wound model.…”
Section: Coating Materials and Excipientsmentioning
confidence: 99%